2020
DOI: 10.1016/j.ijsolstr.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and constitutive relations in the stress-gradient theory: interpretation by homogenization

Abstract: The stress-gradient theory has a third order tensor as kinematic degree of freedom, which is workconjugate to the stress gradient. This tensor was called micro-displacements just for dimensional reasons. Consequently, this theory requires a constitutive relation between stress gradient and micro-displacements, in addition to the conventional stress-strain relation. The formulation of such a constitutive relation and identification of the parameters therein is difficult without an interpretation of the micro-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The vector field u has dimension of a classical displacement. For heterogeneous Cauchy materials that are homogenized as stress-gradient materials, Hütter et al (2020) have recently shown that φ can be interpreted as the trace-free part of the first moment of the microscopic strain-field. The above field equations must be complemented with appropriate boundary conditions…”
Section: Nomenclaturementioning
confidence: 99%
See 2 more Smart Citations
“…The vector field u has dimension of a classical displacement. For heterogeneous Cauchy materials that are homogenized as stress-gradient materials, Hütter et al (2020) have recently shown that φ can be interpreted as the trace-free part of the first moment of the microscopic strain-field. The above field equations must be complemented with appropriate boundary conditions…”
Section: Nomenclaturementioning
confidence: 99%
“…Polizzotto (2018) and references therein. Such models are relevant for nanocomposites exhibiting "negative" size-effect (Tran et al, 2018) and foams (Hütter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new degrees of freedom, called microdisplacements in [14], are conjugate to the stress gradient tensor in the generalised work of internal forces. The microstructural origin of the microdisplacements was recently highlighted based on an original homogenisation approach in [18]. In contrast, the strain gradient model is solely based on the classic displacement degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…This is characteristic for strain gradient theories and in contrast to stress gradient theories in which negative size effects in the sense "smaller is softer" are observed, cf. [10][11][12]. One specific approach to generalised continua is the couple-stress theory, as discussed in detail in [13,14].…”
Section: Introductionmentioning
confidence: 99%